The relationship between anxiety and depression symptoms, and help-seeking intentions in individual sport athletes and university students in Iceland : the moderating role of gender and participant status - Richard Taehtinen 1981- (2017)
This study explored the relationship between anxiety and depression symptoms, and intentions to seek professional help from psychologist, and the moderating role of gender and participant status in this relationship. A total of 375 University students and 187 individual sport athletes, 18 years and older were included in the study. A significant main effect of symptoms on help-seeking intentions was observed among females and this was moderated by participant status; female athletes with depression symptoms reported lower intentions than female students with depression symptoms. There was no main effect of symptoms among athletes, but a significant cross-over interaction effect of symptoms and gender on intentions was observed; non-symptomatic female athletes reported higher intentions than male athletes without symptoms, and female athletes with depression symptoms reported lower intentions than male athletes with depression symptoms. Results suggested that experiencing depression symptoms may decrease female athletes’ intentions to seek help from psychologist.